2013
DOI: 10.1103/physrevstper.9.020117
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in students’ understanding of thermal physics with increasing complexity

Abstract: We analyze the development in students' understanding of fundamental principles in the context of learning a current interdisciplinary research topic-soft matter-that was adapted to the level of high school students. The topic was introduced in a program for interested 11th grade high school students majoring in chemistry and/or physics, in an off-school setting. Soft matter was presented in a gradual increase in the degree of complexity of the phenomena as well as in the level of the quantitative analysis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…In many cases students relate entropy directly (and often incorrectly) to either more familiar thermodynamic quantities (e.g., heat transfer, temperature, work) [2,22], or an imprecisely defined sense of "disorder" [4] when reasoning about entropy changes during particular processes. Langbeheim et al reported similar failures to invoke the 2 nd Law when asking high school students about the signs of entropy changes during phase separation [23]. All of these results imply an incomplete understanding of entropy and how to apply the 2 nd Law.…”
Section: Background Literaturementioning
confidence: 96%
“…In many cases students relate entropy directly (and often incorrectly) to either more familiar thermodynamic quantities (e.g., heat transfer, temperature, work) [2,22], or an imprecisely defined sense of "disorder" [4] when reasoning about entropy changes during particular processes. Langbeheim et al reported similar failures to invoke the 2 nd Law when asking high school students about the signs of entropy changes during phase separation [23]. All of these results imply an incomplete understanding of entropy and how to apply the 2 nd Law.…”
Section: Background Literaturementioning
confidence: 96%
“…In that study, Christensen et al reported several common conceptual difficulties with entropy, including a strong tendency of students to conserve entropy inappropriately, and a tendency to assume that the entropy of all systems must increase, whether or not the system is isolated. Another recent study has used tasks adapted from [7] to probe student understanding of entropy [8].…”
Section: A Previous Researchmentioning
confidence: 99%
“…Los estudiantes con diferentes estilos de aprendizaje revelaron diferencias notables en el logro de aprendizaje, pero no diferencias notables con el aprendizaje significativo, en la conclusión del estudio de (Fan et al, 2015). El análisis de (Langbeheim et al, 2013) sugiere que los conocimientos previos y el marco epistemológico (una combinación de sus tendencias personales y exposición previa a diferentes estilos de aprendizaje) afectan su evolución conceptual.…”
Section: Sobre La Tendencia a Comparar Los Ea Con Diferentes Variablesunclassified